1993
DOI: 10.1086/646645
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Nosocomial Infection: Analysis of Chromosomal Restriction Fragment Patterns by Pulsed-Field Gel Electrophoresis

Abstract: The epidemiological analysis of nosocomial pathogens is a subject of long-standing clinical interest. In recent years, molecular techniques have received increasing attention as a means of analyzing epidemiological interrelationships, thus leading to use of the term molecular epidemiology. Since chromosomal DNA represents a fundamental molecule of cellular identity, there has been particular interest in assessing chromosomal similarity as a measure of epidemiological relatedness.One attractive approach has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
10

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 71 publications
0
59
0
10
Order By: Relevance
“…95 These both need to be assessed more rigorously with GRE collections including those from outbreaks. In recent years, pulsed-field gel electrophoresis (PFGE) has become the method of choice for the epidemiological analysis of many types of nosocomial infection, 96,97 including GRE. 92 However, there are no universally agreed standard criteria for interpreting PFGE banding patterns and there are problems with inter-and intralaboratory reproducibility.…”
Section: Typingmentioning
confidence: 99%
“…95 These both need to be assessed more rigorously with GRE collections including those from outbreaks. In recent years, pulsed-field gel electrophoresis (PFGE) has become the method of choice for the epidemiological analysis of many types of nosocomial infection, 96,97 including GRE. 92 However, there are no universally agreed standard criteria for interpreting PFGE banding patterns and there are problems with inter-and intralaboratory reproducibility.…”
Section: Typingmentioning
confidence: 99%
“…This indicates that the transmission was due to a single epidemic strain. 26,27 The strain TUM1083 was isolated earlier than the other strains. These results suggested that strain TUM1083 was the origin of this outbreak.…”
Section: Aј a A ј Aј A A A ј A A A C B A D A A Bmentioning
confidence: 99%
“…PFGE was applied as a standardized method and interpreted as described earlier (Goering and Tenover, 1997). For MLST, the arcC, aroE, glpF, gmk, pta, tpi, and yqiL genes were amplified by PCR, sequenced, and compared with reference strains as previously described (Enright et al, 2000).…”
Section: Pfge and Mlstmentioning
confidence: 99%